Understanding How Environmental Degradation, Microclimate, and Management Shape Honey Production Across Different Spatial Scales - Vergara-Egert, P; Castro-Morales, S; Quiroz-Espinoza, M; Fierro-Tapia, C; Alaniz-Baeza, A; Carvajal-Leon, M; Hidalgo-Corrotea, C (Springer, 2024)
Although the abundance, survival, and pollination performance of honeybees are sensitive to changes in habitat and climate conditions, the processes by which these effects are transmitted to honey production and interact with beekeeping management are not completely understood. Climate change, habitat degradation, and beekeeping management affect honey yields, and may also interact among themselves resulting in indirect effects across spatial scales. We conducted a 2-year, multi-scale study on Chiloe Island (northern Patagonia), where we evaluated the most relevant environmental and management drivers of honey produced by stationary beekeepers. We found that the effects of microclimate, habitat, and management variables changed with the spatial scale. Among the environmental variables, minimum temperature, and cover of the invasive shrub, gorse (Ulex europaeus) had the strongest detrimental impacts on honey production at spatial scales finer than 4 km. Specialized beekeepers who adopted conventional beekeeping and had more mother colonies were more productive. Mean and minimum temperatures interacted with the percentage of mother colonies, urban cover, and beekeeping income. The gorse cover increased by the combination of high temperatures and the expansion of urban lands, while landscape attributes, such as Eucalyptus plantation cover, influenced beekeeping management. Results suggest that higher temperatures change the available forage or cause thermal stress to honeybees, while invasive shrubs are indicators of degraded habitats. Climate change and habitat degradation are two interrelated environmental phenomena whose effects on beekeeping can be mitigated through adaptive management and habitat restoration. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.